next up previous contents
Next: Regularisation of integral equations Up: M2X, X2X, X2L in Previous: X2X translation formula

   
X2L translation formula

Using the result obtained in J.3 we can obtain the X2L translation formulae given by
$\displaystyle L^1_{j,n,m}(\mbox{\boldmath$ x $ }_0)$ = $\displaystyle \sum_{p=1}^{s(\varepsilon)}\sum_{q=1}^{M(p)} X^1_j(p,q;\mbox{\boldmath$ x $ }_0)
(-i)^m (-\lambda_p/d)^n e^{-i m \alpha_q(p)},$ (K.1)
$\displaystyle L^2_{n,m}(\mbox{\boldmath$ x $ }_0)$ = $\displaystyle \sum_{p=1}^{s(\varepsilon)}\sum_{q=1}^{M(p)} X^2(p,q;\mbox{\boldmath$ x $ }_0)
(-i)^m (-\lambda_p/d)^n e^{-i m \alpha_q(p)}.$ (K.2)



Ken-ichi Yoshida
2001-07-28